2005
DOI: 10.1161/circulationaha.105.552190
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Efficacy of Polymer-Based Paclitaxel-Eluting Stents in the Treatment of Complex, Long Coronary Artery Lesions From a Multicenter, Randomized Trial

Abstract: on behalf of the TAXUS VI InvestigatorsBackground-Intracoronary polymer-based stent delivery of paclitaxel has been shown to be effective in reducing restenosis in simple coronary lesions, but the evidence base for contemporary use in longer, more complex coronary stenoses is lacking. Methods and Results-TAXUS VI is a prospective, multicenter, double-blind, randomized trial assessing clinical and angiographic outcomes of the TAXUS Moderate Release paclitaxel-eluting stent in the treatment of long, complex coro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
136
1
8

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 294 publications
(151 citation statements)
references
References 16 publications
6
136
1
8
Order By: Relevance
“…However, these rates continued to be significantly lower in those who were treated with DES. Finally, the restenosis rates observed in our study were similar to the restenosis rates observed in other studies with systematic angiographic follow-up (6,8,9,13).…”
supporting
confidence: 91%
See 2 more Smart Citations
“…However, these rates continued to be significantly lower in those who were treated with DES. Finally, the restenosis rates observed in our study were similar to the restenosis rates observed in other studies with systematic angiographic follow-up (6,8,9,13).…”
supporting
confidence: 91%
“…Surprisingly, neither group showed any association between stent length and restenosis. This is an unexpected finding since several previous studies have shown a correlation between stent length and/or placement of multiple stents with restenosis, particularly with BMS [1][2][3][4][5][6][7][8][9][10][11][12]. Many of these studies evaluated early generation BMS, comparisons were made to short, focal coronary lesions, and the definition of "long lesions" was conservative compared to our study.…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…Previous studies demonstrated that the rate of restenosis is 7.6-18.9% in patients implanted with paclitaxel-eluting stents (Dawkins et al, 2005;Lansky et al, 2005;Mehilli et al, 2006) and 6.9-14.2% in patients treated with sirolimuseluting stents Kastrati et al, 2005;Mehilli et al, 2006). These results indicated that we need to study more the effects of drug eluting, and it is necessary to seek a new method to prevent restenosis.…”
Section: Introductionmentioning
confidence: 98%
“…Taking the positive long-term results of PCI with adjuvant drug-eluting stent (DES) implantation as compared to subgroups with no stents or bare metal stent implantations into account [11,15,21,22,26], the current use of DES is considered rather restrictive [27,28]. Despite the low percentage of PCI patients receiving DES in Germany (24.0% in 2005 and 29.4% in 2006) the percentage further decreased in 2007 (27.5%).…”
mentioning
confidence: 99%